Kenaikan Pajak Tahun 2024 Bagi Pengusaha UMKM di Kota Surakarta : Tinjauan Sosiologi - Novita Kristina Damayanti (Journal of Development and Social Change, 2025)
In 2022, in Indonesia, there was an increase in the value of VAT tax, which was originally 10% to 11%. Then, in 2024, it has also been planned to increase taxes from entertainment taxes to motor vehicle taxes, and the government has also planned to increase VAT to 12% in 2025. The tax increase is expected to help increase the Indonesian economy. Still, on the contrary, the Indonesian economy, which has not recovered from the pandemic, can cause people to be strangled by the tax increase. This study uses a qualitative research method, with a case study approach. The main data source in the study was through in-depth interviews with informants related to the problem being studied. The results of this study found that tax increases are still not imposed on MSME entrepreneurs in Surakarta City. In its implementation, this tax increase has a negative impact on traders.